(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
This article investigates the main differences and similarities of sentence stress in English and Uzbek from phonetic, functional, and communicative perspectives. Sentence stress plays an essential role in oral speech by organizing information, emphasizing semantic importance, and expressing speaker attitude. The purpose of the study is to compare the characteristics, functions, and patterns of sentence stress in English and Uzbek and to identify their common and distinctive features. The research applies comparative, descriptive, phonetic, and functional methods of analysis. The findings demonstrate that sentence stress in both languages contributes to meaning differentiation, emotional expressiveness, and communicative effectiveness. However, significant differences exist in rhythmic organization, intonation patterns, stress placement, and information structure. The article concludes that sentence stress reflects both universal communicative principles and language-specific phonetic traditions.